The phylogeny, biology and biogeography of the Southern African kelps Ecklonia maxima and Laminaria pallida - Rothman, Mark Dino (Department of Biological Sciences, 2016)
Brown algae of the order Laminariales, commonly referred to as kelps, are the largest and most productive primary producers in the coastal inshore environment. Three genera of kelps are present on the southern African coast: Ecklonia, Laminaria and Macrocystis, of which the first two are ecologically and economically important and the focus of this study. The taxonomy of the genus Ecklonia is investigated. The genus Ecklonia (Phaeophyceae, Lessoniaceae) consists of seven species with four species in the Northern Hemisphere and three in the southern Hemisphere. Ecklonia was recently transferred to the family Lessoniaceae based on phylogenetic analyses of nuclear and chloroplastic markers, though the type of the genus was not included, and its relationship to the allied genera Eckloniopsis and Eisenia remained unresolved. The present study is the first to produce a phylogeny focussed on the genus Ecklonia. It included sequences from nuclear, mitochondrial and chloroplastic DNA, for most of the distribution range of the three current Southern Hemisphere species (E. radiata, E. maxima and a sample of a putative E. brevipes specimen), sequences for East Asiatic species (E. cava, E. kurome and E. stolonifera), as well as the closely related genera Eckloniopsis and Eisenia. Results confirmed E. radiata and E. maxima as two distinct species in South Africa, E. radiata as a single species throughout the Southern Hemisphere (in South Africa, Australia and New Zealand) and East Asiatic species as a distinct lineage from the Southern Hemisphere clade. Results further indicated a close sister relationship between Eckloniopsis radicosa and two Eisenia species (including the type species: Eisenia arborea), and the genus Ecklonia, suggesting that the genera Eckloniopsis and Eisenia are superfluous.